Development of controlled release tablets and evaluation of release behavior for the treatment of Multiple Sclerosis (MS) - Özdemir Akyol, Serenay (Graduate School, 2025)
Polymers have played an integral role in advancing drug delivery technology by providing controlled release of therapeutic agents at fixed doses over long periods of time, cyclic dosing, and adjustable release of both hydrophilic and hydrophobic drugs. In the field of pharmaceuticals, achieving controlled and targeted drug release is of paramount importance. Over the years, researchers and scientists have explored various approches to optimize drug delivery systems. Among these innovative strategies, polymers effect has emerged as a game-changer. Polymers, with their unique propeties and versatile nature, have revolutionized on drug release within the body. The aim of this study is to develop a controlled drug release mechanism for the active ingredient fampridine, used in the treatment of multiple sclerosis (MS), by designing three different prototypes and presenting the release behavior results of fampridine. The first of the prototypes designed for this purpose encompasses modifications to the unit formulation of the reference product, Fampyra (10 mg extended-release tablets, Biogen Pharmaceuticals). This aims to observe the effect of the type and amount of polymer on the release of fampridine in the conventional dry blending process. Fampridine-containing tablets were prepared using the dry blending process and were compressed at 6-6.5 KN, 20 RPM. In vitro release tests were performed using USP Apparatus II (Paddle). The receptor media contained phosphate buffer pH 6.8, and tests were performed under the conditions of 37°C ± 0.5°C, 50 RPM for 24 hours. In vitro release tests were conducted using Waters HPLC with a UV or PDA detector. For the column, Waters Symmetry C18 100×4.6×3.5μ was used. All methods are validated according to ICH guidelines. Different types of Hydroxypropyl Methyl Cellulose (HPMC), known as K100LV, K100M, and K200M, were used as a polymer filler at various ratios in tablet formulations. All results were compared with the reference product, Fampyra. The purpose of this prototype is to determine how much the cellulose-based polymer present in the reference product affects the release of fampridine. It aims to investigate the impact of using different polymers on both the release of fampridine-containing tablets and the morphological characteristics of the tablets. The significance of this prototype lies in its ability to prevent patented excipients in the unit formula of original products from becoming an obstacle in the development of generic drugs, and to create a generic drug formulation that can achieve a similar effect without infringing on patents. Initially, the unit formula of the reference product was used directly; however, different excipients have been included in the unit formula to address the issues arising in the formulation of the generic drug. 1st prototype's results showed that the type and proportion of polymer used in the unit formulation during the conventional dry blending process significantly affect the release of fampridine. As the viscosity of the polymer and its proportion in the formulation increased, adhesive problems occurred in the tablets, making the release of fampridine more challenging. Since delaying the release of fampridine was a desired outcome, aerosil, which has higher effectiveness than Avicel as a diluent in the formulation, was used to resolve the adhesion issues associated with the use of K200M, which has the highest viscosity. The time period during which the fampridine concentration is stabilized in the solvent medium was 12 hours for the reference product, while it has been extended to 18 hours in the revised unit formula of the generic drug formulation. The results are reproducible, and the methods used have been validated according to ICH guidelines. Second prototype delves into both the formulation of bio-based microspheres containing fampridine for the treatment of multiple sclerosis (MS) and provide an alternative way for the commercially available product (Fampyra 10 mg, Biogen). Encapsulation of fampridine was achieved using polyvinyl alcohol (PVA) and two different polymers know as sodium alginate (Na-Alg) and Chitosan (CS). According to the type of microsphere, Glutaraldehyde (GA) and hydrochloric acid (HCl) or glutaraldehyde and sodium hydroxide (NaOH) were used as cross-linking agents. Polymer ratio (PVA: Na-Alg and PVA:CS), drug: polymer (d: p) ratio, cross-linking agent ratio, and cross-linking time were evaluated on fampridine release. Release studies were analyzed using an ultraviole- visible (UV) spectrophotometer. The microspheres were characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and Fourier-transform infrared spectroscopy. (FT-IR). The particle size of fampridine-loaded microspheres were determined by the laser-light-scattering device. The purpose of preparing the second prototype is the lack of any studies in the literature regarding fampridine encapsulated by biological polymers, which have been gaining importance recently. By obtaining microspheres with increasingly effective biological polymers, a comparison of the release behaviors with tablets containing fampridine produced by classical methods has been achieved. This will enable the production of an alternative generic drug using a manufacturing method that does not exist in Turkey or even in the world for fampridine. As for results, the study was seperated into two sections. The first one is PVA:Na-Alg microspheres; it was determined that the highest release of fampridine obtained with microspheres prepared with PVA: Na-Alg (w: w) ratio as 1:1, drug: polymer ratio (w: w) as 1:2, cross-linking agent concentration as 2.5% GA + 3% (v:v) HCl, and cross-linking time as 5 minutes. It was observed that all microspheres have 300- 800 μm particle size and the particule size of the microspheres increases d: p ratio paralelly. The second one is PVA:CS microspheres, the highest release of fampridine obtained with microspheres prepared with a PVA:CS (w: w) ratio as 2:1, drug: polymer ratio as 1:2 (w: w), cross-linking agent concentration as 2.5% (v:v) GA + 1M NaOH, and cross-linking time as 5 minutes. It was observed that the release behavior of microspheres does not conform to Fick's Law, as typically seen in release systems created with hydrogels. The aim of the third prototype was to design oral controlled release osmotic pump tablets of fampridine and optimize the drug release profile using response surface methodology, Box Behnken Method. Ostmotic pump tablets were prepared by direct compression with using variying amount of polyoxhyethylene (PoE) which has different molecular weight (Mw) as 300,000 g/mole and 900,000 g/mole and punched as 1 mm and 2 mm with mini tablet punching machine. Constant amount of Celluloce based Opadry EC (10%) (w: w) was used as coating solution. Formulation of tablets and release optimization evaluated with Box Behnken design. 3 factors and 15 levels were used to optimize drug release profile. PoE amount and hole diameter were taken as the independent variables. Response surface plots and contour plots were drawn, and optimum formulations were selected. The Box-Behnken analysis results showed that the optimum release of fampridine occurred when PoE amount was approximately 300 mg. (Mw=300,000 g/mole), with a 2 mm hole diameter. These results are consistent with existing literature and experimental studies and regarding the kinetic results, all tablets exhibited zero-order kinetic. As for evaluating the release of fampridine in the three designed prototypes, it was found that in the first prototype, the release of fampridine was extended by 6 hours compared to the reference product due to minor changes in the polymer and diluent within the formulation. Although promising results were observed in the other prototypes as well, the differentiation of the generic drug's form from the original drug will necessitate clinical studies. Therefore, it is expected that the efficacy of the microspheres will need to be demonstrated through long-term stability studies and that the clinical trials will yield positive results in order to establish them as an alternative to the reference product. This thesis is significant both in the treatment of MS and in research related to the active ingredient fampridine, as such a comprehensive study has not been conducted before. The methodologies employed aim to enhance the comfort of patients suffering from MS and improve the side effect profile of the medication. If the clinical trials of the designed prototypes against the reference product are successful, this research will provide an alternative therapeutic option accessible to patients.
Multipl Skleroz (MS) tedavisinde kullanılmak üzere kontrollü salım yapan tabletlerin geliştirilmesi ve salım davranışlarının değerlendirilmesi
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2025
Keywords: Multiple Sclerosis (MS); Multipl Skleroz (MS); Release behavior; Salım davranışı; Polymers; Polimerler